Equatorial circular orbits in Kerr–Newman–de Sitter spacetimes - Petr Slaný; Zdeněk Stuchlík (European Physical Journal C: Particles and Fields, 2020)
Abstract Circular motion of test particles in the equatorial plane of the Kerr–Newman–de Sitter (KNdS) spacetime is analyzed for both black-hole and naked-singularity backgrounds. We present relations for specific energy, specific angular momentum and Keplerian angular velocity of a particle on equatorial circular orbit, and discuss criteria for the existence of such orbits giving limits on spacetime parameters. The orientation of motion along circular orbits is discussed from the point of view of locally non-rotating frames. Finally, we discuss the stability of circular motion against radial perturbations and determine limits on the existence of stable circular orbits, as well as the structure of stability regions in KNdS spacetimes.